Be kind - Miller, Pat Zietlow (Roaring Brook Press, 2018)
When Tanisha spills grape juice all over her new dress, her classmate contemplates how to make her feel better and what it means to be kind. From asking the new girl to play to standing up for someone being bullied, this moving and thoughtful story explores what a child can do to be kind, and how each act, big or small, can make a difference or at least help a friend.